Students’ Perception of Using Socrative in Learning Grammar at the English Study Program of FKIP UIR: A Case Study at the Second Year Students - Johari Afrizal; Arimuliani Ahmad; Aini Safitri (J-SHMIC : Journal of English for Academic, 2020)
The main objective of this study is to identify students' perceptions of the implementation of socrative learning grammar. The second-year students of the English Department of FKIP UIR in the academic year 2018/2019 were the objects of this research. Questionnaires and interviews as a tool to collect data for this study. The questionnaire was adapted from the TAM theory (David, Bagozzi & Warshaw, 1989) which included 20 closed questions relating to the perceived usefulness and perceived ease of use of using socrative in learning grammar. The data in this study was analyzed using quantitative and qualitative analysis. While data from the interview were transcribed. The results of this study indicated that students have positive perceptions about the use of socrative. The results of this study also proved that students have a positive view of the use of socrative in learning grammar. This means that they accept the use of socrative in the learning process